BIOECOLOGICAL PROPERTIES OF DRUG MAVRAK (SALVIA OFFICINALIS L.) IN TERMIZ CONDITIONS - Dilbar Kadirova Normuminovna; Khadicha Mirzaeva Yuldashevna (Scholar Express Journal, 2022)
This article is about the bioecological properties of the medicinal plant (Salvia officinalis L.) in the conditions of Termez. Salvia L. belongs to the most widespread family in the world. Its chemical composition includes quinones, essential oils, fatty acids, palmitin, palmitoolein, stearin, olein, linoleic, linolenes and a number of other natural compounds.
Keywords: Medicinal mavrak; Labguldosh; boimorphological; phenological; bioecological and agrotechnical